Multifarious roles of feeding behaviours in rove beetle, Paederus fuscipes - Wan Fatma Zuharah,; Sufian Maryam, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The rice green leafhopper Nephotettix virescens Distant (Hemiptera: Cicadellidae), zigzag leafhopper Recilia dorsalis Motschulsky (Hemiptera: Cicadellidae), and brown planthopper Nilaparvata lugens Stål (Hemiptera: Delphacidae) are the most economically important insect pests infesting rice crop. Paederus fuscipes Curtis has been reported as the natural predator for these rice pest species in Southeast Asia. Under laboratory conditions, we evaluated the prey preference of this generalist predator when it encountered the three main agricultural pests of rice plant. P. fuscipes typically displayed a Type II functional response for all prey species. However, at high prey densities they consumed predominantly R. dorsalis with highest attack rate on dead R. dorsalis prey. Conversely, significantly highest time was needed to handle live R. dorsalis. When various density of preys was tested simultaneously, the predator showed greater preferences towards R. dorsalis and Ni. lugens. We observed the behavioral response of P. fuscipes predator on its prey items. Highest number of searching and capturing attempt was most frequently displayed on live Ni. lugens prey species. Whereas, P. fuscipes spent more feeding time in consuming dead prey compared to the alive ones. Overall, P. fuscipes showed successful control of small and soft body crop pests at low prey density.